Role of Vitamin D & Immunoglobulins E in patients of Seasonal Allergic Conjunctivitis - Samia Sarwar, Saba Iqbal, Nadeem Abbas, Iram Qamar, Shahid Nazeer, Hassan Jamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Allergic conjunctivitis is in fact a bunch of diseases affecting the visual surface and is usually related with type1 hypersensitivity reactions. Two acute disorders, seasonal allergic conjunctivitis and perennial allergic conjunctivitis, exist, as do 3 chronic illnesses, vernal keratoconjunctivitis, atopic keratoconjunctivitis, and giant papillary conjunctivitis. Seasonal allergic conjunctivitis is related with seasonal hypersensitivities that ordinarily happen amid the spring and summer months, and in some cases amid the fall. Exposure to dust, grass and other airborne allergens causes seasonal allergic conjunctivitis. Low levels of vitamin D somewhat related to allergic disorders. This study show a relationship between Serum vitamin D and Immunoglobulin’s E in patients of seasonal allergic conjunctivitis Objective: To evaluate serum vitamin D and serum total immunoglobulin E levels in patients with seasonal allergic conjunctivitis (SAC). Material and Methods Study design: quantitative cross sectional Duration: Six months i.e. 1st September 2021 to 28th February 2022 Data Collection procedure: A cross sectional study was conducted on 100 patients. The study was conducted in Holy Family Hospital Rawalpindi. Ethical approval was taken from ethical committee. An educated consent was taken from the participants. 60 patients in this study presented with seasonal allergic conjunctivitis and 40 healthy normal persons were included. Serum vitamin D and serum total IgE levels were calculated. Results: The average age of the participant in this study was in between 30-50 years of age. In SAC group 40 were males and 20 females. Group two healthy normal consist of 25 males and 15 females. There is a significant decrease of vitamin D level in patients who were diagnosed seasonal allergic conjunctivitis and IgE levels were high when compared to normal healthy group Conclusion: In conclusion, we demonstrated lower plasma vitamin D levels in patients with SAC compared with the control bunch. To conclude a certain association between vitamin D status and allergic conjunctivitis, both multicenter larger case arrangement and further studies examining the impacts of vitamin D supplementation ought to be performed in the long run.